The rapid inhibition of B-cell activation markers by belimumab was associated with disease control in systemic lupus erythematosus patients - Wang, Jing; Ju, Bomiao; Zhu, Li; Li, Hanchao; Luo, Jing; Zhang, Jing; Hu, Nan; Mo, Lingfei; Wang, Yanhua; Pan, Ying; Huang, Jing; Lv, Xiaohong; et al. (Frontiers in Pharmacology, 2023)
Objective: To examine the kinetics of B cell subsets and activation markers in the early stage of belimumab treatment and their correction with treatment response. Methods: We enrolled 27 systemic lupus erythematosus (SLE) patients receiving 6 months belimumab treatment. Flow cytometry was used to test their B cell subsets and activation markers (including CD40, CD80, CD95, CD21low, CD22, p-SYK and p-AKT). Results: During belimumab treatment, SLEDAI-2K declined, the proportions of CD19+ B cells and naïve B cells decreased, whereas the switched memory B cells and non-switched B cells increased. The larger variations of the B cell subsets and the activation markers were in the first 1 month than the other later time frames. The ratio of p-SYK/p-AKT on non-switched B cell at 1 month was associated with the SLEDAI-2K decline rate in the 6 months of belimumab treatment. Conclusion: B cell hyperactivity was rapidly inhibited in the early stage of belimumab treatment, and the ratio of p-SYK/p-AKT may predict SLEDAI-2K decline. Clinical Trial Registration:https://www.clinicaltrials.gov/ct2/show/NCT04893161?term=NCT04893161&draw=2&rank=1; identifier: NCT04893161.